STRENGTHENING THE IMPLEMENTATION OF CHARACTER EDUCATION THROUGH THE TRADITIONAL GAME OF ENGKLEK IN THE THEMATIC LEARNING AT ELEMENTARY SCHOOLS - Astutik, Pipit Pudji (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The increasing cases of juvenile delinquency today, both in terms of quantity and quality, may become an indicator of declining ethics, morals, and character of the nation. This phenomenon, of course, cannot be separated from the role of education, especially in schools. In connection with the issue, the government is currently promoting the strengthening of character education. In the implementation, teachers hold a strategic position. Teachers should be able to make instructional decisions in improving the quality of character-based learning and to choose the right strategy according to the characteristics of the students. At the primary school level, the right learning strategy according to the characteristics of the students, and at the same time supporting character education is using games. Many traditional games are rich in cultural values and national character, such as Engklek . Engklek is a traditional jumping game on a flat field that has been patterned, then the player jumps one foot from one box to the next. The game teaches sportsmanship, togetherness, hard work, and at the same time provides pleasure. In addition, traditional games serve as a counterweight to modern games. Modern games tend to develop the left-brain, the right brain, and creativity. Engklek helps to develop empathy, feelings, and knowing self and nature. Engklek also contains the values of physical development, mental health, social, and problem solving. Based on the description, then the application of traditional games, especially Engklek in thematic learning in schools, can be used as an alternative to strengthen the character education at elementary schools.